Armed Forces of the Future: Going Green? - Stanley-Lockman, Zoe (2017)
Green defence technologies may hold the answer to meeting military requirements for future forces. There are three areas where green defence could enhance operational readiness for armed forces of any size. There are, however, challenges in the implementation of green defence.